Endothelium-dependent vasorelaxant effect of Alchemilla vulgaris methanol extract: A comparison with the aqueous extract in rat aorta - (:unkn) unknown (Taylor and Francis Ltd., 2014)
We aimed to investigate the vascular effects of methanol extract (ME) and aqueous extract (AE) of Alchemilla vulgaris (Rosaceaea). Increasing concentrations of the ME (0.01-10 mg/mL) produced relaxations in noradrenaline (NA: 10-6 M) and K+ (40mM) precontracted aortas while contractions were obtained with the AE (0.01-10 mg/mL). Responses to the ME were inhibited in the presence of putative inhibitors of endothelial vasodilators or after removal of the endothelium. Pretreatment of aortic rings with the ME (10 mg/mL, 20 min) reduced the maximal contractions to NA and K+, whereas an enhanced contractility was observed with the AE (10 mg/mL, 20 min). Total flavonoid content was higher in the ME than in the AE. Quercetin was determined particularly high in the ME while gallic acid was high in the AE. Our results indicated that the ME of A. vulgaris displays favourable vascular effects via endotheliumdependent mechanisms. © 2014 Taylor & Francis.
Keywords: Alchemilla vulgaris extract; endothelium; flavonoid; quercetin; rat aorta; relaxation